The Adoption and Impact of Roman Mail Armor in the Third and Second Centuries BCE - Devereaux, Bret C. (Chiron. Mitteilungen der Kommission für Alte Geschichte und Epigraphik des Deutschen Archäologischen Instituts, 2023)
The Roman adoption of mail armor provided the vector for the spread of what became the most common type of metal body protection west of the Indus River, yet it has received relatively little attention. This paper aims to redress that shortfall by presenting a model, based on archaeological finds, iconographic evidence and literary reports, for the date of Roman adoption of mail from the Gauls as well as the process by which mail replaced the native armor types of Italy to become the standard armor of the legions. It then considers the impact the adoption of mail likely had on Roman military expansion in the second century BCE in light of mail’s defensive capabilities and argues that the superior defensive qualities of mail may explain the relatively light Roman casualties Livy reports for the battles of Magnesia (190) and Pydna (168).